Gambaran Umum Penggunaan Lean Six Sigma Pada Manajemen Obat di RS - Resa Listiani; Faza Duta Pramudyawardani; Nabila Erinaputri; Acim Heri Iswanto (Jurnal Medika Nusantara, 2023)
The hospital pharmacy installation is an important unit in the hospital that is responsible for pharmaceutical activities. Pharmacy is the last unit and one of the important parts that determine patient satisfaction, to improve the service process in operations management, the method that can be used is lean six sigma to help improve service quality and patient satisfaction by minimizing errors and waiting times through organizing and managing the hospital management system. The purpose of this study is to identify an overview of the use of lean six sigma in drug management in hospitals. This research method is a literature review study with the search engine used in literature searches, namely google scholar according to the keywords of the topic to be studied, namely lean six sigma methods, hospital drug management, lean six sigma implementation, the criteria for articles used are based on publications published between 2019 and 2023. The results showed that there is waste in drug/pharmacy management in hospitals. The problems related to pharmacy include too long waiting times, overprocessing of drug prescriptions, and waste of motion in file searches. SIMRS error, lack of trained human resources, uncertainty of drug prices, still done manually are triggers for the occurrence of worthless processes. Waste reduction can be done with the lean six sigma method which can fix problems that often occur in pharmaceutical installations by being applied through standardized calculations.